Non-intrusive drowsiness detection system - Design,analysis and evaluation of non-intrusive driver drowsiness system using a Support Vector Machine and fault diagnosis system - Ashardi Abas (Tanjong Malim, 2011)
Non-intrusive drowsiness detection system - Design,analysis and evaluation of non-intrusive driver drowsiness system using a Support Vector Machine and fault diagnosis system by Ashardi Abas